Trends in the Agarwood industry of Peninsular Malaysia - Desa, Azren Putra; Lee, Shiou Yih; Mustapa, Mohd Zamakhsyary; Mohamed, Rozi; Emang, Diana (Forestry Department Peninsular Malaysia, 2021)
Agarwood is harvested from the forest tree species known as Aquilaria sp. It is considered the most expensive wood due to high demand and widespread use including in medicinal and fragrant products. Therefore, it has great potential to boost the national economy, but its natural population is threatened to extinction due to over-exploitation by illegal agarwood hunters. As a conservation measure, Aquilaria cultivation is established in mass plantations whilst also ensure the availability of agarwood for trade, both at domestic and international markets. From this context, this paper examines the status and development of the agarwood industry in Peninsular Malaysia, one of the largest suppliers of agarwood to the international market. It explores the trends of the agarwood industry, and it also discusses action plans to improve the management in the agarwood industry. Recommendations, based on recent experience and industrial evidence, are made for best practices in improving the state and development of the agarwood industry.